Three-Dimensional Animation of Human Blood Circulation System Using High Poly and Particle System Techniques - Nurcahyani Dewi Retnowati (Institut Teknologi Dirgantara Adisutjipto, 2018)
Circulatory system learning can use three-dimensional animation to facilitate the delivery of material in teaching and learning activities in elementary schools. In making the three-dimensional animation using Autodesk Maya software and 3Ds Max software. The techniques used include High Poly techniques and Particle System techniques. Heart and lung organs, visualized in three dimensions using High Poly techniques while animation of circulatory systems in humans using Particle System techniques. The application function test results indicate that this application can run according to its function and the results of testing the use of applications with the teacher respondents with calculations using a Likert scale obtained results of 97.2% and these results fall into the very good category (using the calculation of interval formulas), so that conclusions are obtained that the three-dimensional animation application of the circulatory system can be applied and can assist the teacher in providing student learning in elementary school.